Fish oil antidepressant-like effects on inflammation and serotonergic system in postpartum depression rat model - Abd Aziz, Nurul Uyun (2020)
The pathophysiology of postpartum depression (PPD) was not well understood. Some studies however managed to strengthen the link between PPD with inflammation and neurochemistry alteration. PPD animals showed increased levels of pro-inflammatory cytokines and alleviated levels of neurotransmitter in brain. Fish oil supplementation reported to decrease the pro-inflammatory cytokines and increase brain neurotransmitter in many depression models of animals including PPD animal model. Fish oil intake reduced depression symptoms by modulating on the serotonergic neurotransmitter (serotonin) and regulation of inflammasome NLRP3 complex. Thus, it was postulated that antidepressant-like effects of fish oil in PPD animal model was influenced by serotonin modulation and NLRP3 inflammasome inhibition. The recent study designed the experiment into two batches (batch A (BA); investigated the effects of 10 days fish oil in PPD rats involvement with NLRP3 complex) and batch B (BB); investigated the effects of 10 days fish oil in PPD rats with the alteration of serotonin (5HT) concentration. The rats were induced to PPD model using hormone simulated pregnancy withdrawal (HSPW) regime for 23 days. The day after 23 days of induction was considered as PPD day 1. All supplements were given for 10 days consecutively. On day 2 and day 10 PPD, force swimming test (FST) and open field test (OFT) were conducted. Rats were sacrificed and brain tissue was collected for serotonin (5HT), histological and inflammasome NLRP3- dependent pro-inflammatory IL-1β analysis. Statistical analysis was evaluated using one-way analysis of variance (ANOVA) followed by the post hoc Tukey’s multiple comparison test with p<0.05 was considered significant. The histological change has been observed using hematoxylin & eosin staining. The results showed that PPD rats without fish oil or fluoxetine showed increased immobility time in FST, NFкB/NLRP3/caspase-1/IL-1β cascade concentration, 5HIAA and 5HT turnover. Supplementation of fish oil or fluoxetine in PPD rats managed to ameliorate the effects of PPD in rats’ hippocampus and PFC. However, the histological findings did not show any significant difference among groups. The PCPA and WAY100135 challenged in PPD rats managed to prevent significant decreased of immobility time in PPD rats with fish oil compared to PPD rats with fish oil without PCPA and WAY100135 injection. It showed that 5HT alteration influenced the antidepressant-like effects of fish oil. Therefore, as a conclusion, the antidepressant-like effects of fish oil in PPD rats given for 10 days were influenced by the modulation of inflammation and serotonergic system.